Teoria e prática dos processos estratégicos: o formal e o emergente na complexidade de uma empresa do setor de telecomunicações - Valgueiro, Murilo Balbino (2009)
This dissertation takes the assumption that it is possible to explain a phenomem throughout the intense exploration of a unique case study, concentrates thus, upon the comprehension of an organizational structure of a firm with national representation as a telecommunications service provider in the Brazilian market. This is obtained by conducting an applied research structured upon a qualitative approach which was carried out by means of semi-structured interviews. The objective of such interviews was to identify the existent factors in the processes of organizational strategies conceptualization which may not allow the birth of emergent strategies. In so doing, the intervenient factors are analyzed in the processes of formal deliberated strategies conceptualization by using the theoretical framework defined in terms of four great theoretical themes: strategy, complexity, decision making and telecommunications sector. The results obtained indicate that in the search for efficiency and efficacy the studied organization uses strong hierarchical control structure (top-down) which offers the opportunity to cyclically review the processes at work, therefore, creating the opportunity to adapt to changes in the reality in which the organization is immersed. On the other hand, as a consequence of the existent unidirectionality in the conceptualization process of developing the formulated strategies, the dates present evidences that there are loss of creativity as well as time in the operational processes to deal with aspects not though carefully during conceptualization. In this sense. the organizational seems not to deal properly with emergent processes that exist in the real organizational practices what may indicate in a loss of opportunity in sustaining competitive advantage as well as to create new ones that can differentiate the services provided by the studied organization.